GP225 Better outcomes of 'high-risk' screened glutaric aciduria type 1 patients give optimism to future cases diagnosed through newborn screening in ireland. (June 2019) - Healy, Lydia; King, Graham; Lawlor, Margeurite; Hughes, Joanne; Knerr, Ina; Treacy, Eileen; Crushell, Ellen; Monavari, Ahmad
Abstract : Introduction: Glutaric aciduria Type 1 (GA1), first described in 1975, has an incidence of approximately 1:56, 000 in Ireland. GA1 usually presents clinically during an intercurrent illness at 3–18 months' age with encephalopathy and dystonia, resulting in dyskinetic/spastic cerebral palsy and sometimes intellectual disability. Management of GA1 involves a low-protein diet with synthetic lysine-free/low-tryptophan protein supplement and L-carnitine treatment, with aggressive management of inter-current illnesses to prevent catabolic crisis and encephalopathy. This review assessed outcomes of high-risk (familial) screened Irish patients versus non-screened patients who presented clinically, prior to the very recent introduction of newborn screening (NBS) for GA1 in Ireland. Method: Retrospective chart review of GA1 patients attending the National Centre for Inherited Metabolic Disorders (1981 – 2018). Data was collected to determine patient clinical and neurological status at diagnosis and at school age. Results: 29 patients were diagnosed with and treated for GA1 during the review period (352 patient treatment years). Thirteen (45%) presented clinically and 16 (55%) were diagnosed early by 'high-risk screen' due to family history. Median age at diagnosis was 365 days (IQR 206–626) for those presenting clinically and 4.5 days (IQR 3–29) for those screened (p<0.001 Mann-Whitney). Six of twelve (50%) patients who presented clinically (one was lost to follow-up) are deceased compared to one patient (6.3%) in the screened group (p=0.008, Chi-squared). Eighteen (62%) patients were from the Irish Travelling Community of which 12 (66.7%) were diagnosed by high-risk screen compared to four of 11 (36.4%) from the non-Traveller population (P=0.111, Chi-squared). Nine of 15 patients (60%) diagnosed by high-risk screen had either radiological only or no features of GA1 at diagnosis, compared to one patient (7.7%) in the clinically presenting group (p=0.004, Chi-squared). Two of the eight patients (25%) presenting clinically who survived to school-age attended mainstream school without significant impairment versus 10 of 14 (71.4%) screened patients (p=0.035 Chi-squared). Three of eight (37.5%) clinical presenters at 5–7 years had either full motor function or a Gross Motor Function Classification System score of 1, compared with all fourteen diagnosed by high-risk screen (p=0.001, Chi-squared). Conclusion: Our data supports the necessity to diagnose infants with GA1 in the newborn period and we expect that future outcomes in the Irish NBS population will be similar to this historical high-risk screening group.